(untitled) (Architecture Image Studies, 2025)
This study examines the intellectual landscape of women’s participation in crea-tive spaces in fostering innovation and advancements toward sustainability. A bibliometric analysis of 1,255 publications from WoS and Scopus published be-tween 2000 and 2024 was conducted using ScientoPy and VOSviewer to analyze an intellectual territory map integrating gender, creativity, and sustainability in understanding the nuances of women’s contributions in creative spaces. The find-ings reveal a clear thematic concentration around creativity and design. Strong collaboration is revealed within design subfields but lacks integration with gen-der-focused scholars. It indicates a critical need to elevate women’s visibility in sustainability-oriented creative research. Recent scholarship has increasingly ad-dressed contemporary issues such as COVID-19, mental health, and social jus-tice, indicating the field’s responsiveness to global challenges. However, sustainability-related terms appear peripheral. It suggests an opportuni-ty for greater integration of these concepts. It highlights the necessity of more tar-geted research and policy interventions that link women’s creative contributions to sustainable development goals, potentially enhancing gender equity and innova-tion in the creative industries. Creative businesses should integrate gender, crea-tivity, and sustainability scholarship into their operational strategies. Promoting mentorship networks of women leaders, creating women-centered creative envi-ronments that empower and support female creators, challenge gender stereo-types, and promote equitable organizational support. Women’s perspectives are essential for advancing inclusive, diverse, and sustainable development in Crea-tive Industries.